To solve this equation, lets move all of the variables to one side of the equation and the constants to the other.
0.12x - 1.5 = 0.24x - 0.06
Subtract 0.12x from both sides of the equation
-1.5 = 0.12x - 0.06
Add 0.06 to both sides of the equation
-1.44 = 0.12x
Divide both sides by 0.12 to isolate x
x = -12
3f + 2g = 30 . . .(1)
f + 2g = 26 . . . .(2)
(1) - (2) => 2f = 4 => f = 4/2 = 2
From (2), 2 + 2g = 26 => 2g = 26 - 2 = 24 => g = 24/2 = 12
Therefore, f = 2 and g = 12
Answer:
y = 5x
Step-by-step explanation:
Step-by-step explanation:
x = 144 ( corresponding angle)
y = 180- 144 ( linear pair)
y= 36°
X + 2/3 = -2(4/5x-7)
Is equivalent to -2(x+2/3)=4/5x-7
So the answer would be A